Efeito hepatoprotetor do óleo essencial de alecrim e gengibre com pré-tratamento em modelo experimental de lesão induzida por paracetamol - Pinho, Rilson José do (2013)
The objective of this study went to investigate and evaluate the hepatic protection and antioxidant effects of the essential oil of ginger (GEO) and rosemary (REO), against hepatic damage in male mice of BALB/c induced by the experimental of liver injury acetaminophen-induced model. The experimental animals have been divided into eight groups with n=5. Each group received by gavage for seven days following treatment: Group (1) control group received no treatment. Group (2) received only vehicle saline containing 0.1% Tween 80, REO or GEO. Groups (3, 4 and 5) received pre-treatment with GEO at doses of 125, 250 and 500 mg/kg. Groups (6, 7 and 8) received pre-treated with REO at doses of 125, 250, and 500 mg/kg. On the seventh day after receiving pretreatment with oil, the animals were fasted for a period of eight hours. After this period animals of Group second to eighth acetaminophen received by gavage at the dose of 250 mg/kg. After 12 h, the mice were anesthetized with halothane, blood was collected to determine plasma markers alanine (ALT) and aspartate aminotransferase (AST) in serum. Sections of liver samples were used to determine the activity of the enzyme myeloperoxidase (MPO). Lipid peroxidation assays were performed in homogenates was used as egg yolk lipid rich medium. The oil GEO and REO were evaluated at concentrations of 0.5, 5.0, 50.0 and 500x10-3 mg/ml. Ascorbic acid was used as positive control. DPPH assays were made with both GEO and REO oils at concentrations from 3.21 to 100 mg/ml. Ascorbic acid was used as positive control. Data were expressed as mean ± SEM for each group. The results were statistically analyzed by analysis of variance (One-way ANOVA) followed by Tukey test. Differences were considered significant at p <0.05. Liver injury induced by acetaminophen, elevated levels of AST and ALT in serum compared to normal control animals. The pretreatment with doses of (500 mg/kg) and GEO and REO for 7 days significantly reduced serum ALT and AST levels as compared to normal controls, but not in doses (125 and 250 mg/kg ) for both oils. MPO activity in mice pretreated with GEO at doses (250 and 500 mg/kg) was significantly decreased (0.046 ± 0.020 and 0.036 ± 0.022 IU/L) when compared with the group of acetaminophen (0.2800 ± 0.600 IU/L). Considering the pretreatment with REO, the doses of (250 and 500 mg/kg) were also effective in reducing MPO activity (0.051 ± 0.056 and 0.01 ± 0.02 IU/L). The RSC GEO at concentrations (12.5 to 100 mg/ml) showed antioxidant activity in vitro with IC50 (32 mg/ml). On the other hand, the RSC REO showed this activity at concentrations (3.12-100 mg/ml) and IC50 (40 mg/ml). In the evaluation of lipid peroxidation GEO showed no significant result in concentrations on the non-enzymatic peroxidation. In the evaluation of lipid peroxidation GEO showed no significant result in concentrations on the non-enzymatic peroxidation. However the concentration of REO (0.5 mg/ml) showed 15% inhibition of lipid peroxidation. The data together suggest that pretreatment with GEO REO and can protect against liver damage promoted by acetaminophen, as well as action against the damage caused by free radicals.